Management Analysis of the Historical Museum Libraries of the Ministerio de Cultura y Juventud of Costa Rica - Ramírez Marín, Carlos Adrián (2012)
The purpose of this research is to identify and document the work of the libraries of the historical museums of the Ministry of Culture and Youth of Costa Rica, so that we can have an overview of this national reality as a starting point for this analysis. In addition, it is intended to provide guidelines for its management, since professionals have found it necessary to direct and initiate museum libraries with conventional library guidelines.